2013
DOI: 10.1002/ece3.549
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing shifts in vital rates driven by long‐term environmental change: a new demographic method based on readily available data

Abstract: Frequently, vital rates are driven by directional, long-term environmental changes. Many of these are of great importance, such as land degradation, climate change, and succession. Traditional demographic methods assume a constant or stationary environment, and thus are inappropriate to analyze populations subject to these changes. They also require repeat surveys of the individuals as change unfolds. Methods for reconstructing such lengthy processes are needed. We present a model that, based on a time series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…We fit inverse models to infer demographic transitions without direct observation of those transitions (Wood ). For example, population size is the outcome of survival, growth and reproduction, and it can be used to infer parameter values for each of these vital rates in stage structured models (González & Martorell ) or in unstructured models (Besbeas, Lebreton & Morgan ). Using the survival and growth parameters inferred above, which is derived from extensive data, along with initial estimates of fecundity parameters, we inferred a fecundity value for all species groups that would (i) reflect approximate long‐term recruitment, so that the species had the potential to contribute to forest structure and (ii) demonstrate low overall sensitivity of dynamics to this estimated recruitment component.…”
Section: Methodsmentioning
confidence: 99%
“…We fit inverse models to infer demographic transitions without direct observation of those transitions (Wood ). For example, population size is the outcome of survival, growth and reproduction, and it can be used to infer parameter values for each of these vital rates in stage structured models (González & Martorell ) or in unstructured models (Besbeas, Lebreton & Morgan ). Using the survival and growth parameters inferred above, which is derived from extensive data, along with initial estimates of fecundity parameters, we inferred a fecundity value for all species groups that would (i) reflect approximate long‐term recruitment, so that the species had the potential to contribute to forest structure and (ii) demonstrate low overall sensitivity of dynamics to this estimated recruitment component.…”
Section: Methodsmentioning
confidence: 99%
“…By imposing bounds (as done by González & Martorell ) or priors on the parameters (or combinations of them), these scenarios can be avoided. However, we did not impose informative priors in our implementation of the inverse procedure, as we wanted to evaluate its ability to correctly reconstruct the vital rates in the absence of any information.…”
Section: Discussionmentioning
confidence: 99%
“…Ghosh, Gelfand & Clark (2012a) used an IPM to reconstruct the vital rates using population structures as input to a similar problem. González & Martorell () attempted an even harder problem: to reconstruct structured vital rates that change over time. These studies have shown that under different assumptions, using inverse modelling is a viable approach to estimate vital rates when only population‐level data are available.…”
Section: Introductionmentioning
confidence: 99%
“…). For example, González and Martorell () obtained maximum‐likelihood estimates of kernel parameters for an IPM of a long‐lived cactus by fitting model simulations to a 12‐year time series of field observations (see also González et al. for a similar approach).…”
Section: Introductionmentioning
confidence: 99%
“…Our approach permits the estimation of uncertain local demographic parameters from a time series of population observations, while accounting for both process and measurement error in those data, and overcomes some limitations faced by prior efforts (Ghosh et al. , González and Martorell , González et al. ).…”
Section: Introductionmentioning
confidence: 99%